Reduction of Perioperative Blood Loss During Endoprosthetic Replacement of Large Joints - D. B. Borisov; S. V. Yudin; O. V. Krylov; B. B. Markov; N. A. Istomina (Общая реаниматология)
Objective: to estimate changes in respiratory and circulatory functions in the acutest period in patients with pulmonary artery thromboembolism (PATE) without arterial hypotension during their first visit. Subjects and methods. The authors analyzed 28 cases of PATE without lowered blood pressure (BP) on primary examination in the prehospital stage (systolic BP (SBP) was less than 100 mm Hg). The study enrolled 17 men and 11 women; their mean age was 67.5±14.5 years. The clinical and ECG pattern was compared on primary examination and over time (following an average of 87±29.7 min). Results. With emergency team care, the rate of tachypnea decreased from 75% on primary examination to 64% over time (p=0.07). Mean respiration rate (RR) fell from 24.0±5.7 to 21.0±5.6 per min (p=0.02). The manifestations of cyanosis were also reduced from 39 to 32% (p=0.4). On primary examination, mean RR, SBP, and diastolic BP were 100.0±19.1 per min, 140.0±21.9 and 80.0±11.5 mm Hg, respectively; after prehospital therapy, these were 100.0±28.2 per min, 130.0±36.8 and 80.0±21.9 mm Hg, respectively (p>0.5). Tachycardia was observed in 60% of the patients both on primary examination and following therapy. One (4%) patient, over time, developed hypotension. ECG analysis revealed an increase in the signs of right cardiac cavity overload. Conclusion. A prehospital fatal outcome was recorded in 1 (4%) patient of those having PATE without arterial hypotension; _ total mortality was 18%. There was progressive deterioration in 32% of the patients due to the progression of both respiratory and cardiovascular failures correctable in the prehospital stage in more than 32 and 39% of cases, respectively. Key words: pulmonary artery thromboembolism, prehospital stage, mortality.